(untitled) (Ukrainian Journal of Ophthalmology, 2025)
The review aims to summarize the current knowledge on the epidemiology, pathogenesis, risk factors, and clinical and diagnostic features of ischemic optic neuropathy. Special attention is focused on the hemodynamic and electrophysiological changes occurring in this disease and the role of brain-derived neurotrophic factor (BDNF) as a potential diagnostic marker of optic nerve damage. The value of current diagnostic techniques (optical coherence tomography, regional hemodynamic studies and electrophysiological techniques) in providing accurate assessment of optic nerve damage is highlighted. Methods: A literature review of 59 publications was conducted.